Reaching Shared Cognition in Business Model Innovation Processes : Overcoming the challenges of an incumbent firm - Daumenlang, Benedikt (My University, 2020)
Business model innovation has long been highlighted as a mean for companies to improve their performance. However, the challenges that incumbent organizations face and how to overcome them, when trying to innovate new business models or change their current one has not received much attention, yet. While smaller and entrepreneurial companies largely benefit from engaging in business model innovation processes, incumbents seem to fall behind in the utilization of such. Path dependencies, the dominant logic of the firm and the interdisciplinary nature of business model innovation are therefore discussed to set a literature frame for business model innovation within incumbents. This thesis proposes to utilize the concept of shared cognition in incumbent firms to be able to over-come the challenges introduced. Executing an in-depth case study with an incumbent case company, attempting to implement an organization-wide business model innovation process offered the researcher insights on the challenges and possible solutions of implementing a business model innovation process within an incumbent firm. Based on the case company results, business model innovation processes in incumbent firms experience a different set of challenges, as opposed to small and medium sized companies or newly found businesses. Internal competition, communication, business model clashes and a disconnection between operational levels and strategical levels of the incumbent are thereby identified. Finally, this thesis explicates the link between organizational strategy formulation and business model innovation, suggesting a process model, specifying the linkage points between the two concepts. Conclusively it is argued, that reaching shared cognition is a precondition as well as part of the solution, specifically in the context of incumbents. Creating this connection offers great potential for improvement. Thereby, this thesis offers possible suggestions for recent calls for linking BMI to organizational strategy as well as addressing the need to explicate the challenges of incumbents engaging in business model innovation and how they might be overcome.